The impact of English usage on social media on college students’ interpersonal communication intentions: a dual mediating model of language confidence and English cultural identity - Zhang, Yichao; Wu, Yiming; Chen, Yanjun; Zhang, Hongtao (Frontiers in Psychology, 2025)
IntroductionSocial media has become part of daily life in the era of globalization and the swift development of internet technology. The worldwide user base is expected to go over 4 billion by 2024, radically transforming social interaction patterns. Being active users of social networks, college students frequently use English on these platforms, and one can expect that their readiness to communicate with others can be affected by such use. Available studies have, however, not explored this relationship holistically. This study examines how the use of English in social media influences college students’ willingness to engage in interpersonal communication, with emphasis on the dual and chained mediation relationships between language confidence and English cultural identity.MethodsThe participants completed an online survey via Questionnaire Star using convenience sampling (n = 412), targeting college students who use English on social media across different universities in the country. The revised Social Media English Usage Scale, Interpersonal Interaction Intentions Scale, Language Confidence Scale, and Cultural Identity items operationalized as English cultural identity were used to gather data. Correlation analyses and descriptive statistics were conducted in SPSS 26.0, and the chained mediation model was tested with the PROCESS macro.ResultsThe findings showed that English use on social media was significantly and positively related to interpersonal communication willingness (r = 0.283, p < 0.01) and directly positively predicted it (β = 0.196, p < 0.001). Three significant indirect pathways were identified: language confidence (effect size = 0.044, 95% CI [0.011, 0.088]), English cultural identity (effect size = 0.038, 95% CI [0.001, 0.082]), and the chain mediation of language confidence → English cultural identity (effect size = 0.005, 95% CI [0.001, 0.015]).DiscussionThese results indicate that English use on social media is related to college students’ willingness to engage in interpersonal communication via both direct and indirect routes. All identity-related findings in this paper refer specifically to English cultural identity; local, multidimensional, or “dynamic” identities were not empirically measured. Such findings provide a framework for studying the relationship between language use and interpersonal communication within social media contexts and have practical implications for educational and platform design.